2016
DOI: 10.1093/geront/gnw091
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Impairment and Affective Symptoms: A Systematic Review

Abstract: Although SCI is consistently related to affective symptoms in older adults cross-sectionally, more longitudinal work is needed to understand their temporal relationship. Improved measurement of SCI would support a deeper understanding of the impact of SCI on psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
145
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(188 citation statements)
references
References 104 publications
23
145
2
9
Order By: Relevance
“…These findings existed regardless of whether we adjusted for subclinical levels of depressive symptoms, which have been found in previous literature to be associated with SCD. 36 An exploratory whole-brain analysis demonstrated an entorhinal-specific FTP-PET association with SCD, supporting this notion of regional specificity. Although SCD was also found to be elevated with a higher Aβ burden, supporting previous study findings, 15,37 this effect was weaker; an interactive effect between tau and Aβ on SCD was not apparent.…”
Section: Discussionmentioning
confidence: 63%
“…These findings existed regardless of whether we adjusted for subclinical levels of depressive symptoms, which have been found in previous literature to be associated with SCD. 36 An exploratory whole-brain analysis demonstrated an entorhinal-specific FTP-PET association with SCD, supporting this notion of regional specificity. Although SCD was also found to be elevated with a higher Aβ burden, supporting previous study findings, 15,37 this effect was weaker; an interactive effect between tau and Aβ on SCD was not apparent.…”
Section: Discussionmentioning
confidence: 63%
“…However, the inclusion of SCC as a core diagnostic feature has been questioned, given the inconsistent relationship between self-reported SCC and objective cognitive functioning in MCI (Lenehan, Klekociuk, & Summers, 2012; Roberts, Clare, & Woods, 2009; Ryu, Lee, Kim, & Lee, 2016). This weak relationship is further attenuated by at least two factors: (1) individuals with objective cognitive impairment may demonstrate anosognosia or reduced awareness of their cognitive decline (Galeone, Pappalardo, Chieffi, Iavarone, & Carlomagno, 2011; Hill et al, 2016; Roberts et al, 2009; Starkstein, 2014; Vogel et al, 2004), leading them to underestimate or under-report SCC; and (2) self-reported SCC in older adults have been found to be more strongly related to emotional factors such as depression and anxiety (Buckley et al, 2013; Ryu et al, 2016; Slavin et al, 2010; Studer, Donati, Popp, & von Gunten, 2013; Yates, Clare, & Woods, 2017) and personality characteristics such as neuroticism (Reid & MacLullich, 2006; Slavin et al, 2010), than to actual cognitive ability which may lead cognitively normal individuals to overestimate or over-report cognitive problems.…”
Section: Introductionmentioning
confidence: 99%
“…The context of comparison, specifically in reference to one’s self over time or in reference to others, demonstrates differential associations with aspects of psychological well-being. This holds important implications, particularly given the well-established links between subjective memory and affective symptoms (Hill et al, 2016). Disentangling these complex relationships is key to identifying intervention targets: poor subjective memory ratings may indicate the need for more extensive mental health screenings, or alternatively, the introduction of cognitive strategies and supports to maintain everyday functional ability.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective memory is influenced by a multitude of factors beyond actual memory performance. Regardless of objective memory performance, poorer subjective memory is frequently linked to increased psychological distress (Buckley et al, 2013; Chin, Oh, Seo, & Na, 2014; Minett, Da Silva, Ortiz, & Bertolucci, 2008); however, this literature has focused on the relationship of subjective memory and depressive symptoms without considering other aspects of psychological well-being (e.g., life satisfaction, Hill et al, 2016). Additionally, no studies have examined whether different approaches to the assessment of subjective memory differentially predict psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation